A "Mitsubishi emblem" tetrauclear aluminum complex containing two unsymmetric N2O2‐ligands and a symmetric NO3‐ligand as initiator for polymerization of rac‐lactide. Issue 12 (8th April 2017) - Hu, Minggang; Wang, Fugui; Han, Fuzhong; Deng, Qigang; Ma, Wenhui; Yan, Hailong; Dong, Guohua; Song, Weiming
ABSTRACT: A novel hydroxy‐, methoxy‐, and phenoxy‐bridge "Mitsubishi emblem" tetranuclear aluminum complex (1 ) is synthesized from an unsymmetric amine‐pyridine‐bis(phenol) N2 O2 ‐ligand (H2 L 1 ) and a symmetric amine‐tris(phenol) NO3 ‐ligand (H2 L 2 ). Two same configuration chiral nitrogen atoms are formed in the tetranuclear Al complex upon coordination of the unsymmetric tertiary amine ligand to central Al. Complex1 initiates controlled ring‐opening polymerization (ROP) of rac ‐lactide and afford polylactide (PLA) with narrow molecular weight distributions ( M w / M n  = 1.05–1.19). The analysis of 1 H NMR spectra of the oligomer indicates that the methoxy group is the initiating group and the ring‐opening polymerization of lactide follows a coordination‐insertion mechanism. The Homonuclear decoupled 1 H NMR spectroscopy suggests the isotactic‐rich chains is preferentially formed in PLA. The study on kinetics of the ROP of lactide reveals the homopropagation rate is higher than the cross‐propagation rate, which is in agreement with the observed isotactic selectivity in the ROP of rac ‐lactide. The stereochemistry of the polymerization was also supported by activation parameters. The introduction of unsymmetric ligand H2 L 1 has an effect on stereoslectivity of polymerization. This result may be of interest for the design of multinuclear metal complex catalysts containing functionalized ligands. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2084–2091 Abstract : A novel hydroxy‐, methoxy‐, and phenoxy‐bridged tetanuclear "Mitsubishi emblem" aluminum complex is synthesized. The complex is capable of initiating the ring‐opening polytmerization of rac ‐lactide to yield isotactic‐rich polylactide with very narrow polydispersity indexes. The kinetic studies reveal the homopropagation rate is higher than the cross‐propagation rate, and the observed isotactic selectivity in the polymerization of rac ‐lactide is also supported by activation parameters.